Cost of disorders of the brain in Spain. - Oleguer Parés-Badell (Public Library of Science (PLoS), 2014)
Background Brain disorders represent a high burden in Europe and worldwide. The objective of this study was to provide specific estimates of the economic costs of brain disorders in Spain, based on published epidemiological and economic evidence. Methods A cost-of-illness study with a societal perspective of 19 brain disorders was carried out. Cost data published between 2004 and 2012 was obtained from a systematic literature review. Direct healthcare, direct non-medical and indirect costs were considered, prioritizing bottom-up information. All costs were converted to Euro and to year 2010. The missing values were imputed with European estimates. Sensitivity analyses based on qualitative assessment of the literature and on a Monte Carlo simulation were performed. Results The review identified 33 articles with information on costs for 11 disorders (8 neurological, 3 mental). The average per-patient cost ranged from 36,946 € for multiple sclerosis to 402 € for headache. The societal cost of the 19 brain disorders in Spain in 2010 was estimated in 84 € billion. Societal costs ranged from 15 € billion for dementia to 65 € million for eating disorders. Mental disorders societal cost were 46 € billions (55% of the total), while neurological disorder added up to 38 € billion. Healthcare costs represented 37% of the societal costs of brain disorders, whereas direct non-medical constituted 29% and indirect costs 33%. Conclusion Brain disorders have a substantial economic impact in Spain (equivalent to almost 8% of the country's GDP). Economic data on several important brain disorders, specially mental disorders, is still sparse.